L’empire de la valeur. Quelle critique de la théorie (néo)-walrassienne ? - Claire Pignol (Revue de la Régulation)
The Empire of Value proposes a criticism of walrasian utility theory and offers a substitute through the alternative assumption of mimetic desire. This critic is examined in three steps. First, we discuss the identification and interpretation that Orléan proposes of the walrasian assumptions: preferences’ objectivity and convexity; consumer’s sovereignty. Second, we examine the impact of the mimetic assumption’s consequences on equilibrium efficiency and stability. Third, we reword this criticism in terms of questioning instead of assumptions and results. This questioning concerns both the agents’ frustration and the social world’s pacification that can be deduced from.